Actinopyga atypica sp. nov. plus two new holothuroid records from the coastal waters of Pakistan (Echinodermata: Holothuroidea) - Ahmed, Quratulan; Thandar, Ahmed S.; Ali, Qadeer Mohammad; Shaikh, Iqra (Zootaxa, 2026)
A new species, Actinopyga atypica sp. nov., in the sea cucumber family Holothuriidae, plus two new holothuroid records from the Pakistan coastal waters are here described. The new species differs from all known species of Actinopyga in possessing a cucumariid-type of calcareous ring accompanied by slender, straight, terminally forked rods in the body wall, unlike the thick, usually well-branched rods of other species of the genus, setting it apart from all known congenerics. Of the two additional records one is another holothuriid herein attributed to the Indo-West Pacific species Holothuria (Selenkothuria) erinacea Semper, 1868. It is suspected to be a juvenile of this species in possessing, in addition to the perforated rods and plates in the body wall, well-formed tables, suspected to be a juvenile character, as pertains in its consubgenerics H. (S.) parva Krauss (in Lampert, 1885) and H. (S.) moebii Ludwig, 1883. The third species is a thyonid, Thyonina bijui Thandar, 2017, belonging to the family Thyonidae (sensu Smirnov 2012), originally described from Kerala, India.